Frugal Living dengan nilai Ajaran Al-Qur'an Sebagai Solusi Pola Hidup Konsumtif : Studi Atas Ayat-ayat tentang Larangan Berlebihan - Amaliya, Niila Khoiru Amaliya; Lilia Indiana Sari (Program Studi Ilmu Al-Qur'an dan Tafsir, 2025)
The phenomenon of consumerism has become one of today's contemporary social problems. Consumerism impacts the economic stability of individuals and families. In addition, consumerism also reflects unhealthy social behavior and mental health. The frugal living lifestyle, which is a pattern of saving and being wise in consumption, has emerged as a new paradigm to respond to consumerism. On the other hand, the Qur'an as a book of guidance for life also has teachings on how to consume, especially with the concept of balance, not being stingy and not being wasteful. This study aims to analyze the integration of the concept of frugal living with the values ​​of the Qur'an as an alternative solution in building a moderate and conscious lifestyle and consumption behavior. The research method used is a literature study with a thematic approach (mawḍū‘ī) to relevant Qur'anic verses, such as QS. al-Isrā' (17): 27, QS. and QS. al-A‘rāf (7): 31. The results of the study indicate that the value of frugal living has a strong correlation with the Qur’anic principles of al-iqtishād (simplicity), al-infaq al-mu‘tadil (moderate spending), and the prohibition of isrāf (excessive spending). This integration is not only able to reduce consumer behavior, but also fosters spiritual awareness, social responsibility, and environmental sustainability. This study recommends the implementation of frugal living values ​​based on Qur’anic ethics in education, families, and public policy as a preventive measure against modern consumer culture.